The fire chronicle [compact disc, unabridged] - Stephens, John, 1972- (Stephens, John, 1972- Books of beginning, 2012)
"In the second book in the Books of Beginning Trilogy, Michael and Emma must track down the Chronicle of Life, while Kate must find a way back to present day from the year 1899"--